SGLT2 Inhibitors in Patients with Urogenital Malformations and Urinary Diversions: Risks, Benefits, and Clinical Considerations - Mohammed Abdulrasak; Ali Someili; Mostafa Mohrag (Medicina)
Background: Sodium-glucose cotransporter-2 inhibitors (SGLT2i) are increasingly used in patients with type 2 diabetes, chronic kidney disease, and heart failure. However, their safety and efficacy in patients with congenital or surgically altered urogenital anatomy remains underexplored. Methods: We conducted a narrative review of current evidence regarding the use of SGLT2i in patients with urinary tract malformations, urinary diversions, and functional voiding disorders. Key risks, clinical considerations, and management strategies were synthesized from the existing literature and case reports. Results: Patients with benign prostatic hyperplasia, vesicoureteral reflux, neurogenic bladder, nephrostomies, and ileal conduits may face increased risks of urinary tract infections, fungal colonization, and therapy-related complications due to persistent glycosuria and altered urinary flow. Nevertheless, these patients may still benefit from SGLT2i’s systemic renal and cardiovascular effects. Individualized risk assessment, close monitoring, and multidisciplinary management are essential. Conclusions: Patients with urological abnormalities represent a high-risk but potentially high-reward population for SGLT2i therapy. A cautious, tailored approach is necessary, and future dedicated research is urgently needed to better guide clinical practice.